2018
DOI: 10.1177/0300060518800588
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of IL-6, IL-8, and IL-10 are indicators of prognosis in pancreatic cancer

Abstract: ObjectiveEarly detection and prognosis prediction are critical to improve patient survival in pancreatic cancer. This study aimed to investigate whether interleukins could serve as indicators of prognosis in pancreatic cancer.MethodsSixty-eight patients with pancreatic cancer were enrolled in the study during the period between 2012 and 2014. The serum levels of a broad spectrum of interleukins in these patients were determined, including IL-1β, IL-2, IL-6, IL-8, IL-10, IL-13, IL-15, and IL-23.ResultsIL-6, IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 42 publications
9
60
0
Order By: Relevance
“…The results in (Figure 1) showed a signi icant increase [p<0.001, p<0.002, p<0.01] in the level of interleukins (IL-4, IL-6, IL-8) in ovarian cancer patients compared to the healthy control group. These results were in agreement with those performed by others (Feng et al, 2018) which they found that serum interleukins increased in cancer patients compared to normal ones. A large number of studies propose that factors linked to the in lammation of the ovarian surface epithelium are correlated with an elevated risk for epithelial ovarian cancer (EOC).…”
Section: Resultssupporting
confidence: 93%
“…The results in (Figure 1) showed a signi icant increase [p<0.001, p<0.002, p<0.01] in the level of interleukins (IL-4, IL-6, IL-8) in ovarian cancer patients compared to the healthy control group. These results were in agreement with those performed by others (Feng et al, 2018) which they found that serum interleukins increased in cancer patients compared to normal ones. A large number of studies propose that factors linked to the in lammation of the ovarian surface epithelium are correlated with an elevated risk for epithelial ovarian cancer (EOC).…”
Section: Resultssupporting
confidence: 93%
“…Elevation of serum IL-6 is a negative prognostic marker in human PDAC Serum IL-6 levels were increased in PDAC patients compared with healthy patients [69,[152][153][154][155][156][157][158] or those with chronic pancreatitis [152,154,157,158], and were also increased in patients with metastatic PDAC compared to those with locally advanced disease [157][158][159][160][161]. Moreover, elevated serum IL-6 positively correlated with increased disease burden, weight loss/cachexia, and metastasis [69,[152][153][154][155][156][157][158][159][160][162][163][164][165][166][167], however, there are conflicting observations in the literature regarding IL-6 and cachexia [161]. Although, increased serum IL-6 levels correlate with increased disease stage, and in metastatic patients correlates with poor overall survival [161,168].…”
Section: Interleukin 6 In Pdacmentioning
confidence: 99%
“…IL-8 was first discovered as a leukocyte chemotactic factor and since then emerged as a double-edged sword of inflammation (Beck et al, 2016;Hammond et al, 1995;Long et al, 2016;Sallusto and Baggiolini, 2008;Singer and Sansonetti, 2004). Further, IL-8 has emerged as a crucial factor in mediating tumour angiogenesis, tumour cell survival and metastasis (David et al, 2016;Feng et al, 2018;Itoh et al, 2005;Li et al, 2003;Waugh and Wilson, 2008;Xu and Fidler, 2000). Intriguingly, the effect is kinase-independent and we demonstrated that ERK3 controls the transcription factor AP-1/c-Jun in both, HCPECs and HT-29 cells ( Figure 6D-6E and Figure 6G, respectively).…”
Section: Discussionmentioning
confidence: 99%